2022
DOI: 10.1039/d2nr01160c
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and standardization of extracellular vesicle measurements by flow cytometry for translational prostate cancer research

Abstract: Extracellular vesicles (EVs) are microscopic particles released naturally in biofluids by all cell types. Since EVs inherits genomic and proteomic patterns from the cell of origin, they are emerging as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Despite the relevance of our findings, this study has some limitations that need to be considered. First, tumor EV-DNA and EV-RNA are subject to dilution among non-tumoral EV in circulation, same as ctDNA is diluted in non-tumoral cell-free DNA (17,34,41,42). In our study, we focused in late-stage prostate cancer patients, where the proportion of tumor related circulating material is expected to be higher.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the relevance of our findings, this study has some limitations that need to be considered. First, tumor EV-DNA and EV-RNA are subject to dilution among non-tumoral EV in circulation, same as ctDNA is diluted in non-tumoral cell-free DNA (17,34,41,42). In our study, we focused in late-stage prostate cancer patients, where the proportion of tumor related circulating material is expected to be higher.…”
Section: Discussionmentioning
confidence: 99%
“…EVs were analyzed using an Apogee A60 Micro Plus system (A60MP, Apogee Flow Systems Inc., Northwood, UK) as previously described. , Briefly, anti-CYP2E1 and anti-AFP Abs were conjugated with Alexa Fluor 488 (AF488) and Alexa Fluor 647 (AF647) antibody labeling kits (Thermo Fisher Scientific, Waltham, MA), respectively. For sample preparation, 5 μL of EV samples (10 10 particles/mL) were incubated with 10 μL of anti-CYP2E1@AF488 and anti-AFP@AF647 with desired concentrations (18 μg/mL in PBS for both antibodies).…”
Section: Methodsmentioning
confidence: 99%
“…Single EV analysis may be accomplished using several approaches including flow cytometry, Raman spectroscopy, and optical trapping. These methods have allowed analysis of the size, shape, content, and biological activity of individual EVs. Flow cytometry is arguably the most commonly used approach for quantitative and compositional analysis of single EVs. , It has been used, for example, to characterize EV subsets produced by colorectal cancer cell lines and platelets. However, flow cytometry and other single EV analysis approaches provide only limited information on the relative abundancies of biomarkers. Despite the recent progress, there remains a need for technologies for high-throughput and multiplexed analysis of single EVs that also allow for quantification of EV marker expression.…”
Section: Introductionmentioning
confidence: 99%
“…Each of the studies developed EV measurement methods. Kim et al ( 2022 ) first proposed a systematic method using standardized and calibrated flow cytometry for the quantification of PCa-derived EVs from blood and urine with detailed methodologies, instrument characteristics and acquisition settings. Their study validated the effectiveness of this method and demonstrated that PSMA+ EVs and STEAP+ EVs might be surrogate markers for metastatic PCa.…”
Section: Introductionmentioning
confidence: 99%